Influence of Motivation on Millennial Tourist Satisfaction and Re-Visit Intention at Glamping in Kintamani District, Bangli Regency, Bali - Swariga, I Made; Wijaya, Ni Made Sofia; Indrawati, Yayu (Green Publisher Indonesia, 2023)
The COVID-19 pandemic has an impact on the tourism industry, Bali is one of the places affected because most of the people work in the tourism industry, during the COVID-19 pandemic. Kintamani is one of the tourist destinations that is still visited by many tourists, especially domestic tourists, the development of tourism in the pandemic era has triggered the emergence of new trends in the world of tourism such as glamping business (glamour camping). This study aims to determine the effect of motivation can increase the intention of tourists to stay again in addition to affecting tourist satisfaction. The method used is a quantitative approach and uses a qualitative approach to describe the characteristics of respondents and the scale assessment given by respondents. Data collection techniques in this study use questionnaires, then sampling techniques using accidental sampling. The data analysis technique used in this study is quantitative descriptive, then hypothesis testing using smart PLS software. The results of this study concluded that based on the t-test, t-statistical value of each variable in this study, there was a positive direct influence between motivation (X) on satisfaction (Y1), motivation (X) on the re-visit intention (Y2), satisfaction (Y1) on the re-visit intention (Y2), and the indirect influence that satisfaction (Y2) was able to mediate motivation (X) and re-visit intention (Y2) from all hypotheses both direct and indirect influences Exogenous variables on endogenous variables have a significant positive influence, namely having a p-value less than (0.05) and having a t-statistic value greater than (1.96).